Patient-related risk factors for in-hospital functional decline in older adults: A systematic review and meta-analysis. (12th February 2022) - Geyskens, Lisa; Jeuris, Anthony; Deschodt, Mieke; Van Grootven, Bastiaan; Gielen, Evelien; Flamaing, Johan
Abstract: Background: Functional decline (FD) is a common and serious problem among hospitalised older adults. Objective: This systematic review and meta-analysis aims to identify patient-related risk factors for in-hospital FD in older adults. Methods: Previous reviews on this topic (1970-2007) and the databases PubMed, Embase, and CINAHL (January 2007-December 2020) were searched. Reference lists of included articles were screened. Studies investigating patient-related risk factors for FD from (pre)admission to discharge in older adults admitted to an acute geriatric or internal medical unit were included. Study quality was assessed using the modified Newcastle-Ottawa Scale. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were estimated using random-effects models. The quality of evidence was assessed using GRADE. Results: Twenty-nine studies met the inclusion criteria. Statistically significant risk factors were living in a nursing home (OR, 2.42; 95% CI, 1.29-4.52), impairment in instrumental activities of daily living (OR, 2.08; 95% CI, 1.51-2.86), history of falls (OR, 1.71; 95% CI, 1.00-2.92), cognitive impairment (OR, 1.83; 95% CI, 1.56-2.14), dementia (OR, 1.71; 95% CI, 1.23-2.38), delirium (OR, 2.34; 95% CI, 1.88-2.93), (risk of) malnutrition (OR, 1.76; 95% CI, 1.03-3.03), hypoalbuminemia (OR, 1.79; 95% CI, 1.36-2.36), comorbidity (OR, 1.09; 95% CI, 1.03-1.16), and the presence of pressure ulcers (OR, 3.33; 95% CI, 1.82-6.09). The narrative synthesis suggested prehospital FD, needing assistance with walking, and low body mass index as additional risk factors. Conclusions: Several patient-related risk factors for in-hospital FD were identified that can be used at hospital admission to identify older patients at risk of FD.